Saw-palmetto: an Ecologically and Economically Important Native Palm - George W. Tanner; J. Jeffrey Mullahey (EDIS)
Revised! WEC-109, a 4-page fact sheet by George W. Tanner and J. Jeffrey Mullahey, describes this major understory plant endemic to the southeastern United States — description, associated plants, ecological importance, management and use, managing fruit production. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, February 2009.